2021
DOI: 10.3390/fluids6070252
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Study of the Hydrodynamic Characteristics of a Torpedo-Shaped Underwater Glider

Abstract: In this study, numerical computation is used to investigate the hydrodynamic characteristics of a torpedo-shaped underwater glider. The physical model of a torpedo-shaped underwater glider is developed by Myring profile equations and analyzed by the computational fluid dynamics approach. The Navier–Stokes equations and the energy equation coupled with the appropriate boundary conditions are solved numerically by using Comsol Multiphysics software. The numerical results contribute to the major part of reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Based on large eddy simulation and the Ffowcs-Williams and Hawkings equations, Qin et al [32] performed hydrodynamic analysis for a Slocum glider and a blended-wing-body glider, and concluded that blended-wing-body gliders have lower energy cost and low noise performance. Le and Hong [33] used computational fluid dynamics (CFD) methods to acquire the hydrodynamic characteristics of a torpedo-shaped underwater glider, demonstrating the practicality of CFD methods in glider design. To reflect the underwater glider motion more realistically, Wang et al [34] proposed a fluid-multibody coupled analysis method considering the interactions between multibody dynamics and fluid dynamics, enabling a complex dynamic analysis of the underwater glider.…”
Section: Introductionmentioning
confidence: 99%
“…Based on large eddy simulation and the Ffowcs-Williams and Hawkings equations, Qin et al [32] performed hydrodynamic analysis for a Slocum glider and a blended-wing-body glider, and concluded that blended-wing-body gliders have lower energy cost and low noise performance. Le and Hong [33] used computational fluid dynamics (CFD) methods to acquire the hydrodynamic characteristics of a torpedo-shaped underwater glider, demonstrating the practicality of CFD methods in glider design. To reflect the underwater glider motion more realistically, Wang et al [34] proposed a fluid-multibody coupled analysis method considering the interactions between multibody dynamics and fluid dynamics, enabling a complex dynamic analysis of the underwater glider.…”
Section: Introductionmentioning
confidence: 99%
“…Computer fluid dynamic (CFD) simulation is one of the most common ways to obtain hydrodynamic parameters of underwater * Corresponding author. E-mail address: hchoi@kmou.ac.kr equipment easily and quickly in the research process of underwater equipment [8][9][10][11][12]. Nguyen et al [13] have proposed a robust adaptive control algorithm for the hybrid underwater glider (HUG).…”
Section: Introductionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) is known as an important technology for the study of the hydro-aerodynamic characteristics of fluid motion, and has been applied to a microchannel, sterilization chamber, torpedo-shaped underwater glider, centrifugal blower, an infection isolation room, etc. [7][8][9][10][11][12][13][14]. Le et al [7][8][9][10] investigated the thermocapillary migration of the fluid flows in a microchannel.…”
Section: Introductionmentioning
confidence: 99%